Faktor-Faktor Yang Berhubungan Dengan Kejadian Berat Bayi Lahir Rendah (BBLR) Di Klink Rosalina Munthe Tahun 2025 - Ratih Widya Wati Gultom; Diah Karlina (VitaMedica : Jurnal Rumpun Kesehatan Umum, 2025)
Low Birth Weight (LBW) is a condition in which a newborn weighs less than 2.5 kg, generally caused by premature birth (<37 weeks) or intrauterine growth restriction. LBW increases the risk of health problems such as growth delays, cognitive impairments, infections, respiratory disorders, cardiovascular issues, gastrointestinal problems, kidney disorders, and higher rates of infant morbidity and mortality. This study aimed to identify factors associated with LBW in the working area of Rosalina Munthe Clinic. The study used an analytical design with a cross-sectional approach, and data were analyzed using univariate and bivariate methods with SPSS. Results showed that 33.3% of respondents had LBW infants. Mothers with unsafe age were 39.7%, those with unsafe pregnancy intervals were 61.9%, low socioeconomic status was found in 66.7%, and low educational level in 81%. Analysis revealed a significant association between maternal age and LBW incidence. However, pregnancy interval, anemia, and socioeconomic status showed no significant association with LBW. This study highlights that maternal age plays a key role in LBW occurrence, while other factors require further investigation to understand their contribution to the risk of delivering low birth weight infants.